Fgf10 Signaling-Based Evidence for the Existence of an Embryonic Stage Distinct From the Pseudoglandular Stage During Mouse Lung Development - Taghizadeh, Sara; Jones, Matthew R.; Olmer, Ruth; Ulrich, Saskia; Danopoulos, Soula; Shen, Chengguo; Chen, Chaolei; Wilhelm, Jochen; Martin, Ulrich; Chen, Chengshui; Al Alam, Denise; Bellusci, Saverio (Frontiers in Cell and Developmental Biology, 2020)
The existence during mouse lung development of an embryonic stage temporally and functionally distinct from the subsequent pseudoglandular stage has been proposed but never demonstrated; while studies in human embryonic lung tissue fail to recapitulate the molecular control of branching found in mice. Lung development in mice starts officially at embryonic day (E) 9.5 when on the ventral side of the primary foregut tube, both the trachea and the two primary lung buds emerge and elongate to form a completely separate structure from the foregut by E10. In the subsequent six days, the primary lung buds undergo an intense process of branching to form a ramified tree by E16.5. We used transgenic mice allowing to transiently inhibit endogenous fibroblast growth factor 10 (Fgf10) activity in mutant embryos at E9, E9.5, and E11 upon intraperitoneal exposure to doxycycline and examined the resulting lung phenotype at later developmental stages. We also determined using gene arrays the transcriptomic response of flow cytometry-isolated human alveolar epithelial progenitor cells derived from hESC or hiPSC, grown in vitro for 12 or 24 hours, in the presence or absence of recombinant FGF10. Following injection at E9, the corresponding mutant lungs at E18.5 appear almost normal in size and shape but close up examination indicate failure of the right lung to undergo lobar septation. At E9.5, the lungs are slightly hypoplastic but display normal differentiation and functionality. However, at E11, the lungs show impaired branching and are no longer functional. Using gene array data, we report only a partial overlap between human and mouse in the genes previously shown to be regulated by Fgf10 at E12.5. This study supports the existence of an embryonic stage of lung development where Fgf10 signaling does not play a function in the branching process but rather in lobar septation. It also posits that functional comparisons between mouse and human organogenesis must account for these distinct stages